Práticas docentes de educação artística para o desenvolvimento da participação e diálogo: um estudo com os/as educandos/as do Proeja no Instituto Federal do Espírito Santo - Cavati, Verônica da Silva Cunha (2013)
This thesis investigated the contribution of theater games as educational practice in the National Programme for Integration of Professional Education with the Basic Education in Terms of Education for Youths and Adults (Proeja) at the Federal Institute of Education, Science and Technology of Espírito Santo (also called Espírito Santo Federal Institute - Ifes). The theoretical emplacements of the research were based on works of Paulo Freire and Augusto Boal. In that sense, the books Pedagogy of the oppressed (1968, Brazil), by Freire, and Theater of the oppressed and other poetic policies (1975, Brazil), by Boal, were special. As methodological procedure, we opted for a qualitative approach directed by the participant research, which prioritizes the subject in his relationship with the object and the different viewpoints of the participant women and participant men. The research was conducted with 25 students (educandas and educandos) from the Proeja. The activities were developed in the art room of the Ifes, through exercises and image games that are from the Theater of the Oppressed. The results showed that the theater games are an important way for participation and dialogue. It is a means of developing speech, of seizures exchange of life experienced by all the community. Between educandas and educandos it was observed the development of body expression, installation and expansion of dialogical relationship, perception of self and other and was clear the concern together to seek solutions to the problems experienced. The research adds knowledge to the field of study about the curriculum, in a critical perspective, presenting the possibility of building new teaching practices at the interface with practices of arts education